Model Simulation of Forearm Hyperaemic Reactivity - Zhao, Xueli; Arsenault, Andre; Lavoie, Kim L.; Meloche, Bernard; Bacon, Simon L. (CMBES Proceedings, 2007)
Forearm hyperaemic reactivity (FHR) has been proposed as a novel noninvasive method for discriminating patients with cardiovascular disease (CVD). However, the modeling functions of FHR require more robust models. The present study was designed to develop quantitative modeling techniques to better estimate the physiology of this model. The fitted time activity curves of the hyperaemic arm of non- CVD participants, using blood and muscle uptake, were obtained in the 2-compartment model with the mean R2=0.913±0.018. However, for CVD patients, the 2- compartment model yielded a mean R2=0.844±0.018, so a 3-compartment model was used. This model generated mean R2 of 0.982±0.002 for non-CVD participants and 0.979±0.002 for CVD patients. It is believed that 3- compartment model provides estimates of the activity in the blood, in the interstitial space or cytoplasm, and in the mitochondria. The 2-compartment model provides good fits for FHR in non-CVD participants but not CVD patients. Alternatively, it would seem that the 3-compartment model provides good fits for both groups. These results should help us optimize the predictive values of the FHR test, infer pathological components of the disease and, ultimately improve the patient risk stratification.